The Impact of E-Cigarettes on Oral Injuries and Bone Fractures - Karen Głogowska; Mikołaj Wojtas; Julia Piątkiewicz; Maria Krzyżanowska; Marcin Kapica; Gabriela Nowak; Aleksandra Żmijewska; Mateusz Sztybór; Monika Maleszewska; Wojciech Kopacz (Kazimierz Wielki University, 2024)
Introduction The rising prevalence of electronic cigarette (e-cigarette) use has prompted concerns regarding its potential health implications. While much attention has focused on respiratory and cardiovascular effects, injuries, oral trauma, and bone fractures linked to e-cigarette use have received less scrutiny. This paper aims to comprehensively review the landscape of injuries, oral trauma, and bone fractures induced by e-cigarettes, shedding light on this underexplored facet of e-cigarette-related harm. Material and Methods This literature review has analyzed 16 papers. Inclusion criteria: researches and case reports published after 2015. PubMed and Google Scholar has been searched to identify the papers.  Analysis of the Literature Existing literature suggests a growing incidence of injuries, oral trauma, and bone fractures associated with e-cigarette use, albeit with limited systematic investigation. Mechanisms underlying these injuries range from device malfunctions to inadvertent impacts during use. Case reports highlight a spectrum of injuries, including oral burns, dental trauma, and skeletal fractures, often involving the face and mouth regions. Conclusions Despite the lack of comprehensive epidemiological data emerging evidence underscores the need for heightened awareness and preventive measures to mitigate e-cigarette-related injuries. Enhanced education, regulation of e-cigarette devices, and promotion of safer usage practices are crucial steps towards reducing the burden of e-cigarette-related harm on oral and skeletal health.